Qualidade de vida de pacientes oncológicos com dor - Souza, Isabela Cristina Antunes de (2024)
Objective: To analyze the quality of life of oncology patients with pain. Methods: Observational, analytical, quantitative study conducted from September 2022 to February 2023. Data collection included sociodemographic and clinical information, as well as the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30). The study included patients undergoing antineoplastic treatment who experienced pain at least once in the past week, had the physical and cognitive ability to answer simple questions, and willingly participated in the study by signing the informed consent form. The pain level was classified using the Visual Analog Scale (VAS) with three levels (mild 1-2, moderate 3-7, and intense 8-10). A total of 120 participants were included, recruited from the Clinical Oncology Service of a teaching hospital in the state of São Paulo. Sociodemographic and clinical data were analyzed using descriptive statistics. Exploratory analysis employed descriptive statistics, Mann-Whitney test, Kruskal-Wallis test, and Spearman correlation, with a significance level of 5%. The study was approved by the Research Ethics Committee (CEP) under opinion no: 5461238 and CAAE: 58397522.9.0000.5415. Results: 60.0% of participants were female, with a mean age of 59.8 years; 63.3% had no history of alcoholism, and 55.8% had no history of smoking. The most prevalent oncological diagnoses were breast cancer (27.5%), colon and rectum (17.5%), and hematologic tumors (16.6%). 72.5% of diagnoses were made within the past year, and 53.3% of participants had some metastasis. Despite undergoing pain treatment, 76.6% of participants did not experience complete relief and continued to live with pain. 60% used non-opioid medications. According to the EORTC QLQ-C30 analysis, a statistically significant difference was observed in the functional scale (p = 0.039). When evaluating the correlation between the instrument scales and pain, a significant difference was noted in all three assessed scales, with directly proportional values in the symptom scale (r = 0.371). It was observed that the reported pain level and symptoms directly impact the quality of life. Conclusion: Despite being prevalent in most oncology patients, pain is often inadequately managed. Living with pain significantly impacts the quality of life of both patients and their families. Understanding the influence of pain on the quality of life of oncology patients is a crucial step for interventions to be focused on the most negatively affected areas. Oncology patients with good quality of life are more likely to cope better with the disease and exhibit better physical and psychological conditions during treatment. Health professionals should be aware of this influence and be prepared to promote better coping conditions through education, medication reconciliation, and physical encouragement.